TINGKAT PENYESUAIAN DIRI ANAK YANG TINGGAL DI PANTI ASUHAN (Studi Pada Panti Asuhan Baiturrahmah Desa Rimbo Panjang Km.17 Kecamatan Tambang Kabupaten Kampar) - Pipit Suwita; Basri " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study aims to determine how tingkatpenyesuaian child who lived in the orphanage Baiturrahmah and the factors that influence the adjustment of children in the orphanage Baiturrahmah Live. The theory used is the theory of the development of the theory or learning-oriented environment. This study is associated with the three factors put forward by Burhanuddin (1999), namely frustration, conflict, and anxiety. Researchers conducted the study at the Orphanage Baiturrahmah to determine the level of adjustment of children in the orphanage Baiturrahmah. Data collection techniques by distributing data obtained from questionnaires and further if by using SPSS. Data collection techniques in this study is a census, which is taken from all respondents who are in the orphanage. From the results of research in the field that the factors that influence the adjustment seen from frustrating to have a score of 550, the anxiety has a score of 542, the conflict had a score of 537, with the recapitulation of the overall respondents obtained a score of 1629 in the category of the absence of factors that influence the adjustment of children living in Orphanage Baiturrahmah. But not with the results per individual respondents, as many as 21 children or 31% stating that the factors that influence the adjustment of children living in the orphanage Baiturrahmah. And the level of children's adjustment to the environment has a score of 609, the peer has a score of 627, the caregiver has a score of 592 and the school has a score of 498, with the recapitulation of the overall respondents obtained a score of 2326 with a very high category. But not with the results per individual respondents, as many as 27 children or 39.7% which states that the factors affecting the level of adjustment of children living in the orphanage Baiturrahmah in terms of factors of frustration, anxiety, conflict.Keywords: Adjustment, Foster Children, Orphanage